PRODUCTIVITY OF SUGAR BEET DEPENDING ON THE CALCULATED FERTILIZER NORMS FOR THE PROGRAMMED YIELD ON DARK GREY PODZOLIC SOIL - Parkhuts , Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
This study presents the results of examining the effects of calculated fertilizer norms on the anticipated yields of 55, 60, and 65 t/ha of sugar beet of Panda hybrid grown on dark grey podzolic soil in the Western Forest-Steppe of Ukraine. The experimental setup included the following variants: control (without fertilizers); recommended norm for this zone N120P160K170 (1.00 : 1.33 : 1.42); calculated fertilizer norm N173P209K253 (1.00 : 1.21 : 1.46) for a programmed yield of 55 t/ha; calculated fertilizer norm N189P228K276 (1.00 : 1.21 : 1.46) for a programmed yield of 60 t/ha; calculated fertilizer norm N204P247K299 (1.00 : 1.21 : 1.46) for a programmed yield of 65 t/ha. Approximate correction factors were utilized for the calculations to ensure plants receive the necessary nutrients - nitrogen fertilizers at 0.7, phosphorus fertilizers at 1.0, and potassium fertilizers at 1.0. The average consumption rates of the main nutrients for the formation of 1 ton of crop yield are as follows: N – 4.5 kg, P2O5 – 3.8 kg, K2O – 4.6 kg. The highest yield of 64.8 t/ha with an increase to the control of 32.1 t/ha, or 98 %, on average over the years of research, was obtained when applying mineral fertilizers at the calculated norm of N205P247K299. When the calculated norm of N189P228K276 was applied, the yield was 60.2 t/ha with an increase of 27.5 t/ha, or 84 %, compared to the control variant. When applying the calculated norm of N173P209K253, the yield was 54.6 t/ha with an increase of 21.9 t/ha, or 67 %, compared to the control variant. When the recommended norm of N120P160K170 was applied, the yield was 48.5 t/ha with an increase of 15.8 t/ha, or 48 %, compared to the control variant. The lowest sugar beet yield of 32.7 t/ha was obtained in the control variant of the experiment – without fertilization. The highest sugar content of 17.6 % was obtained in the control variant, and its total yield of 10.36 t/ha was obtained with the application of the calculated norm of mineral fertilizers of N205P247K299 for a programmed yield of 65 t/ha. The lowest sugar content was obtained with the calculated norm of N205P247K299 – 16.0 %. In the control variant, the sugar yield was the lowest and amounted to 5.75 t/ha. The highest net profit of 41771 UAH/ha and a profitability level of 98.6 % was achieved with the application of the calculated norm of N205P247K299.